Problems of Nationalism: Corruption and Power Abuse in National and State Life - fatma, sandriea (Journal of Strategic Behaviour Accounting, 2025)
Corruption and abuse of power are serious challenges in government and society. Corruption is rooted in the abuse of power that occurs without transparency and strict oversight. The negative impacts of corruption not only harm the state financially, but also undermine public trust in government institutions and exacerbate social inequality. Efforts to prevent corruption can be made through stricter law enforcement, education from an early age, oversight by the public and the media, and increased transparency in administration and finance. Case studies in residential areas show that responsible and transparent leadership plays a crucial role in rebuilding public trust in institutions or communities affected by the abuse of power. Additionally, policy-based approaches such as the Corruption Risk Assessment (CRA) implemented in South Korea and tax reporting mechanisms like Tax Receipt in Australia have proven effective in enhancing transparency and reducing corruption opportunities. Through a combination of stricter regulations, government ethics education, and active public participation, corruption can be significantly curbed to create a cleaner and more accountable governance system.